Analisis dan Pengembangan Sistem Pemesanan Makanan Berbasis Website untuk Mendukung Operasional Café - Elaine Elaine; Fendy Sanjaya; Richard Halim; Sunario Megawan; Mirza Ilhami (Universitas Methodist Indonesia, 2024)
This research aims to develop a web-based Point of Sales (POS) system that can support online food ordering processes and computerized inventory management. The background of this research focuses on the importance of implementing technology in cafés, particularly in supporting business processes such as structured ordering systems, food stock management, and evaluating sales and food stock reports. The research methodology consists of a comprehensive analysis of the existing ordering system at Loving Nature Fortunate Coffee through visitor surveys, staff interviews, and direct observation of operational processes. The results of this research show that the implementation of a web-based Point of Sales (POS) system at Loving Nature Fortunate Coffee can increase the operational efficiency of the café and make business processes more structured and systematically recorded.